Comparação das alterações dimensionais lineares em modelos de gesso pedra tipo IV obtidos de moldes de siliconas de condensação e de adição em períodos diferentes de vazamento - Fares, Nasser Hussein (2012)
Dimensional stability of two silicones impression materials, condensation and addition, was assessed regarding poured periods. A metal master model was constructed with two implant abutments with same height, diameter and same distance between the abutmens. Eighty models of the master model were obtained with the two times impression technique. All partial aluminum stock tray were relieved in 1 mm. The sample was divided in two groups: 1) 40 models acquired by condensation silicone and 2) 40 models acquired by addition silicone. The dental stone type 4 were poured before molding at periods: 30 minutes, 24 hours, 72 hours andn one week. The OrthoAnalyzer-2010 was used to measure three zones of each abutment: oclusal diameter, height and distance between the abutments. The data was analyzed and results were better at periods 30 minutes and 24 hours with both materials. The condensation silicone can be well utilized provided the poured period should be at least 24 hours.